Volume 9: Oil and Gas Applications; Supercritical CO2 Power Cycles; Wind Energy 2017
DOI: 10.1115/gt2017-63707
|View full text |Cite
|
Sign up to set email alerts
|

Cycle Modeling and Optimization of an Integrally Geared sCO2 Compander

Abstract: This paper presents the selection of a system configuration and off-design control method for an integrally geared compander based on cycle modeling and optimization. The goal of the cycle modeling was to determine a cycle configuration that would reach an efficiency of 50% at design conditions and to optimize off-design control to maintain high efficiencies. The compander is being developed for use in a concentrated solar power supercritical carbon dioxide power plant with expected turbine inlet temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Nevertheless, it has been observed that the compressor inlet volumetric flow is higher than the design point volumetric flow at higher CIT when the cycle is optimised for maximum efficiency. This observation is in line with Bennett et al [53] and the trend is expected to depend on the shape of the compressor map.…”
Section: Multi-objective Optimisation For Off-design Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, it has been observed that the compressor inlet volumetric flow is higher than the design point volumetric flow at higher CIT when the cycle is optimised for maximum efficiency. This observation is in line with Bennett et al [53] and the trend is expected to depend on the shape of the compressor map.…”
Section: Multi-objective Optimisation For Off-design Performancesupporting
confidence: 92%
“…18 shows these parameters when maximising the net power. A linear increase in the efficiency above the design value is observed when the CIT is lower than 42 °C, which is similar to the observations of Schmitt et al, and Bennett et al [42,53]. The maximum power optimisation reached 105% of the design value, which is set as the maximum bound for the power.…”
Section: Annual Performancesupporting
confidence: 87%
“…The study, which is described more fully in Refs. [1] and [2], was performed iteratively with turbomachinery aerodynamic design calculations, resulting in a four-stage reheated expander, twostage main compressor, and two-stage recompressor. The turbomachinery was incorporated into a single integrally geared machine with a main compressor first-stage design point inlet condition of 37 C and 85 barA.…”
Section: Cycle Considerationsmentioning
confidence: 99%
“…Temperature rise is suppressed in the former thus power consumption becomes smaller than in the latter. There are several key technologies such as (i) Rotordynamic design (ii) High pressure casing design (iii) High pressure gas seal (iv) Aerodynamic component design for high pressure operation including super critical area and (v) Impeller blade strength design, which has to be implemented in order to employ integrally geared compressors for high pressure gas compression usage, such as Carbon Capture and Storage (CCS), Urea plant and S-CO 2 Power Cycle (Bennett et al, 2017). The progress of these technologies is nowadays remarkable and enables integrally geared compressors to get into high pressure applications more than 20 MPaG.…”
Section: Introductionmentioning
confidence: 99%